Analisis Urgensi Manajemen Mutu Terpadu Terhadap Eksistensi Gereja Di Era Normal Baru - Djone Georges Nicolas (Jayapangus Press, 2021)
The Covid-19 pandemic has shaken the world with its phenomenal effects. No exception, the Indonesian church, worship has been shifted from church buildings to houses, the style of worship from face-to-face shifted to virtual, technology recording which is the primary need seems to have shocked the church. it becomes a problem because it is outside the custom that has been adopted so far. What can the churches do to keep its existence relevant? This research aims to determine the urgency of integrated quality management in the church in facing the New Normal with the Covid 19 Pandemic, so that it remains relevant and exists. The research approach is qualitative with descriptive methods using the Integrated Quality Management (MMT) system. The data technique used several instruments: interviews, observation and literature documentation. The research subjects were congregations at the Bethel Indonesia Church Parakletos Taman Palem Lestari Cengkareng, West Jakarta. The conclusion is that, everyone in fact, and needs the best in everything, including among the churches.